PERAN LSM DALAM MELAKUKAN ADVOKASI TERHADAP KEBIJAKAN PEMERINTAH - Muhammad Fiqri Fadillah; Aidin Aidin (Jurnal Studi Ilmu Pemerintahan, 2021)
This research has focused on the role of a non-governmental organization that advocates against the PAUD policy in management are still many forms found differences in the delivery of educational systems. This research method is qualitative descriptive. The results of this research to find out which social Practices undertook NGOs is a form of Colored Poor relations of duality based on her theory of structural discussed by Giddens.